Resiliensi Prajurit TNI: Peran Makna Kerja dalam Mendukung Performa Prajurit - Dirgantara, Muhamad Irhas; El Hami, Azhar (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2025)
Indonesian National Armed Forces (TNI) is the primary component of the nation's defense and frequently encounter demanding, dynamic, and high-risk situations. This research aims to investigate the influence of meaning in work on the resilience of TNI personnel in support of their performance. The methodology employed in this study is a quantitative correlational design utilizing simple linear regression analysis, involving 255 TNI personnel within combat units. The findings indicate that the perceived meaningfulness of their work significantly impacts the resilience of TNI personnel. Resilient TNI personnel are better equipped to adapt, recover, and grow in stressful circumstances, and are more capable of exhibiting optimal cognitive, emotional, and tactical performance in their duties. Keywords: Meaning of Work; Resiliency; Military